Prediction model of adult flight activities of Synanthedon bicingulata (Lepidoptera, Sesiidae) - Hyeon-Ji Yang; Seonwoong Nah; Hyunjung Kim; Sunghoon Baek (Heliyon, 2025)
Clearwing moth, Synanthedon bicingulata, was first reported in 1931 in Korea, but its economic damage has been suddenly increasing with the climatic change. However, a prediction model for the adult occurrence of S. bicingulata has not yet been developed. Thus, this study was aimed to develop a forecasting model for adult occurrence and to predict its future occurrence. The historical flight activity data of S. bicingulata were fitted with the two-peaked Weibull function against its developmental degree-days with the lower developmental threshold, 4 °C, and the bio-fixed date, October 1 in the previous year. The developed model well predicted its historical emergence in field conditions. When the model was applied to climate change scenarios, it was expected that the future occurrence of S. bicingulata could become earlier than the current. Thus, the results of this study should be helpful in managing S. bicigulata populations.